MPeat—A fully coupled mechanical‐ecohydrological model of peatland development. Issue 1 (6th October 2021) - Mahdiyasa, Adilan W.; Large, David J.; Muljadi, Bagus P.; Icardi, Matteo; Triantafyllou, Savvas
Abstract: Mathematical models of long‐term peatland development have been produced to analyse peatland behaviour. However, existing models ignore the mechanical processes that have the potential to provide important feedback. Here, we propose a one‐dimensional model, MPeat, that couples mechanical, ecological and hydrological processes via poroelasticity theory, which couples fluid flow and solid deformation. Poroelasticity formulation in the MPeat is divided into two categories, fully saturated and unsaturated. To validate this formulation, we compare numerical solutions of the fully saturated case with analytical solutions of Terzaghi's problem. Two groups of MPeat simulations are run over 6, 000 years using constant and variable climate, and the results are compared to those of two other peat growth models, DigiBog and the Holocene Peat Model. Under both climatic conditions, MPeat generates the expected changes in bulk density, active porosity and hydraulic conductivity at the transition from the unsaturated to the saturated zone. The range of values of peat physical properties simulated by MPeat shows good agreement with field measurement, indicating plausible outputs of the proposed model. Compared to the other peat growth models, the results generated by MPeat illustrate the importance of poroelasticity to the behaviour of peatland. In particular, the inclusion of poroelasticity produces shallower water table depth, accumulates greater quantities of carbon and buffers the effect of climate changes on water table depth and carbon accumulation rates. These results illustrate the importance of mechanical feedbacks on peatland ecohydrology and carbon stock resilience.